Climate change: Behavioral responses from extreme events and delayed damages - Riccardo Ghidoni; Giacomo Calzolari; Marco Casari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
Understanding how to sustain cooperation in the climate change global dilemma is crucial to mitigate its harmful consequences. Damages from climate change typically occurs after long delays and can take the form of more frequent realizations of extreme and random events. These features generate a decoupling between emis- sions and their damages, which we study through a laboratory experiment. We find that some decision-makers respond to global emissions, as expected, while others respond to realized damages also when emissions are observable. On balance, the presence of delayed/stochastic consequences did not impair cooperation. However, we observed a worrisome increasing trend of emissions when damages hit with delay.
Keywords: C70; C90; D03; Q54; 330; Social dilemma; Experiments; Greenhouse gas; Pollution